Penyuluhan Perilaku Hidup Bersih dan Sehat (PHBS) dalam Menjaga Kebersihan Lingkungan pada Masyarakat Desa Serigeni Baru - Ratna Dewi; Arigo Pramana; Bobby Fernando; Eva Dwi Yanti; Veoni Novsetri Jonata; Ulli Sari Pransiska; Risky Amey Yolanda; Darma Yunita; Devara Alya Danisa; Kurnia Arsela; Agita Aulia; Vonia Atlia; Didi Jhondiani; Dika Maharani (JURNAL PENGABDIAN KADER BANGSA, 2026)
Environmental health is one of the factors influencing the overall health status of the community, particularly in rural areas that still face challenges in waste management and the implementation of Clean and Healthy Living Behavior (PHBS). Counseling activities serve as an educational approach to guide communities in maintaining environmental cleanliness. This activity aimed to describe the implementation of PHBS counseling in maintaining environmental cleanliness among the community of Serigeni Baru Village. The method used was a community service activity with an evaluative approach using a one group pretest–posttest design. The activity was conducted at the Village Head’s residence for approximately 45 minutes with a total of 30 participants. The results showed that the activity was carried out in an orderly manner and received active participation from the community. Evaluation results indicated an increase in knowledge level, where the proportion of participants in the good category increased from 6 people (20%) in the pretest to 20 people (67%) in the posttest, while the poor category decreased from 14 people (47%) to 3 people (10%). Participants were also actively involved in discussions and able to restate the material delivered. It can be concluded that the PHBS counseling was well implemented and effective in improving community knowledge and supporting efforts to promote environmental cleanliness at the village level.